Effect of walking and bone joint exercise on enhancing bone remodeling in menopausal women: A randomized controlled trial - Pasa, Chusairil; Pamungkasari, Eti P.; Doewes, Muchsin; Purwanto, Bambang; Hartono, Hartono; Cilmiaty, Risya; Dirgahayu, Paramasari (Narra Sains Indonesia, 2024)
Osteoporosis increases fracture risk and reduces quality of life in menopausal women. Although physical activity, such as walking and bone joint exercise, is known to help maintain bone health, its effectiveness needs further examination. The aim of this study was to analyze the effects of physical activity, in particular walking and bone joint exercise, on enhancing bone remodeling in menopausal women. A randomized controlled trial was conducted among menopausal women and allocated into three groups: walking, bone joint exercise, and control groups. The intervention was provided for eight weeks, with the outcomes measured before and after the intervention. The study assessed five bone remodeling biomarkers: estrogen, parathyroid hormone (PTH), receptor activator of nuclear factor kappa-β ligand (RANKL), tumor necrosis factor-alpha (TNF-α), and bone mineral density (BMD). The paired sample student t-test and ANOVA were used to assess the effects of the interventions. The results indicated that, compared to pre-intervention, both walking and bone joint exercise significantly increased the estrogen (p=0.026 and p=0.023, respectively), decreased RANKL (p=0.019 and p=0.002, respectively), decreased PTH levels (p=0.022 and p=0.048, respectively) and increased the BMD scores (p=0.001 and p<0.001, respectively). In the control group, none of the remodeling biomarkers significantly changed except the mean level of TNF-α, which was increased significantly (p=0.001). This study highlights that structured exercise, such as walking and bone joint exercise, can significantly enhance bone remodeling markers in menopausal women. Therefore, implementing such physical activities into management may provide benefits to menopausal women.